Evaluation of Glass Ionomer Cements (GICS) properties with coumarin derivatives as antibacterial agent - Mohamad, Dasmawati (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2017)
Glass Ionomer Cements (GIC) are widely used as dental restorative materials due to their aesthetics features and fluoride content. However, a capability of fluoride content in GIC to inhibit bacteria growth in an oral environment was insufficient for a long term which may leads to secondary caries. Therefore, the objective of this research was to fabricate a new GICs with coumarin derivatives as an antibacterial agent. :3-Acetylcoumarin (1) and hydrazine thiosemicarbazide coumarin derivatives (2) have been successfully 5ynthesized at laboratory scale. Their structural identification was confirmed by Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR) analysis. Both synthesized compounds were fabricated with GICs at percentage of 0.5, 1.0, 1.5, 2.0 and 2.5. The antibacterial activities of tested materials were assessed by agar diffusion test (ADT) and bacteria growth. The effect of incorporation of 3-acetylcoumarir (3-AC) on the mechanical properties and surface morphology of glass ionomer cement (GIC) were evaluated. Flexural strength of the specimens were analysed using Shimadzu AGX-Pius while morphological evaluation of the specimens were observed using Scanning Electron Microscope. An ill· vitro cytotoxicity study of the synthetised coumarin derivatives were screened using a 3-(4,5· dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MIT) assay on Human Periodontal Ligament Fibroblast (HPDLF) cells. Release profile of 3-Acetylcoumarin (GIC-1) and hydrazinyl thiosemicarbazide of coumarin derivatives (GIC-2) at three different concentrations of 0.5, 1.0 and 1.5 % were evaluated using Microplate Reader up to 30 days. Both synthesized coumarin derivatives showed very promising properties as an antibacterial agent to be incorporated with GIC.